The can't cook book : 100+ recipes for the absolutely terrified! - Seinfeld, Jessica (Atria Books, 2013)
"Many smart, accomplished people don't know how to cook--and they feel embarrassed and anxious about not being successful in this area of their lives ... But cooking doesn't have to scary or stressful, even if you've never read a recipe or used your oven. Jessica will show you how to prepare the deliciously simple food you love to order in restaurants: from caesar salad, butternut squash soup, and roasted asparagus to lemon salmon, roast chicken, and pasta with clams. Each recipe is written in Jessica's calming, confidence-building voice, which tells you up-front what the challenge will be and then shows you exactly how you overcome it in easy-to-follow, step-by-step instructions"--